Nommer les dieux hittites: au sujet de quelques épithètes divines - Mouton, Alice (Archiv für Religionsgeschichte, 2020)
After a short overview of Hittite divine epithets (Anatolia of the second half of the second millennium BCE), this paper explores the attestations of two particular divine names, namely “the bloody god U.GUR” and “the vengeful nakkiu-/nakkiwa‐s.” These entities are studied in context in order to determine their identity and functions. Through this contextual analysis, it appears that these supernatural entities are held responsible for various anomalies in the context of Luwian rituals probably coming from the Lower Land (south-central Anatolia).